Research and Improvement on K-means Algorithm Based on Large Data Set (International Journal of Engineering and Computer Science, 2017)
The highway safety is being cooperated and there are not sufficient safety aspects by which we can examine the traffic crashes before it occurs. A technique is planned by which we can pre-process the unintentional aspects. In order to control these pre-process issues, a clustering technique is used. In clustering technique present k-mean algorithm is improved and this improved K-mean algorithm will apply on traffic dataset. This dataset is composed from National Highway Authority. To collect data in the dataset several assessments and surveys are conducted from people and the staff of National Highway Authority. The elementary impression of this proposed work is to develop highway safety